Ramsay Hunt Syndrome: A Rare Disease of Multiple Cranial Nerve Involvement - Al Mamun, Md Abdullah; Islam, Md Rabiul; Majumder, Riashat Azim; Mondal, Mowpiya; Moniruzzama, Md; Mahbub, Md Rashid E; Ashaduzzaman, Mohammad (Mugda Medical College Journal, 2024)
Ramsay Hunt Syndrome (RHS) also known as herpes zoster oticus is a viral disease, a member of the human herpes virus family, is a late complication of varicella-zoster virus infection that results in inflammation of the geniculate ganglion of cranial nerve VII. Ramsay Hunt is a clinical diagnosis. The hallmark of the condition is multiple unilateral erythematous vesicles, which are distributed over the auricle and preceded by severe otalgia. If these symptoms are associated with facial nerve palsy, the condition is called RHS which is usually accompanied by vestibulocochlear abnormalities. Diagnosis is often missed or delayed, which can lead to an increased incidence of long-term complications. The condition is self-limiting, but treatment is targeted at decreasing the total duration of the illness as well as providing analgesia and preventing the complications that can occur. This activity reviews the role of the inter professional team in the diagnosis and treatment of RHS. Mugda Med Coll J. 2024; 7(1): 48-52